Understanding the factors contributing to low enrollment of science students in undergraduate programs - Sadef Khan; Maria Shiraz; Gulzar Shah; Maham Muzamil (Cogent Education, 2023)
AbstractThe pursuit of science is essential for the progress and development of a nation. However, there is evidence of a persistent decline in the number of students opting for science courses in undergraduate programs across the world. This paper investigated the perceptions of the students regarding the reasons for the dearth of science students and why science students switch their majors after the completion of 12 years of education (Intermediate level) in Pakistan. A sequential mixed-methods analysis comprising a survey of a convenience sample of 101 undergraduate students and qualitative interviews with 6 science faculty were used for data collection in the City of Lahore. The findings from quantitative data analyses indicated that the major factors associated with the dearth of science students are favorite subject (<0.05), lack of access to well-trained science teachers (<0.09), parents’ wishes against science subjects (<0.03), and poor grades (<0.001). The qualitative data from science teachers showed that reasons for lack of interest in science subjects include the lack of experts in science fields in Pakistan, the quality of science textbooks, the norm of rote memorization of scientific concepts, the annual examination system (as opposed to semester or quarter) and lack of refresher courses for science faculty. The study concluded that a complex set of individual, interpersonal, and institutional factors act as reasons (barriers or facilitators) for students’ lack of interest in science as a field of college-level education.